The use of imperative mood in standard turkish - Mousa, AbdulWahab K.; Rafeq, Rafeq S.; Ali, Dilbreen A. (Humanities Journal of University of Zakho, 2016)
The use of imperative mood is widely used in everyday life. This study attempts to cast light on the use of the imperative mood in the Turkish language on the purpose of knowing them in the Kurdish language. After a theoretical research about this subject has been done, it appeared that, in the Turkish Grammar, grammarians see the subject differently, only a few few grammarians believe that the imperative mood can be used with the (first, second and third persons), whereas the majority of some other grammarians affirm that it is only used with the second, and third person singular and plural, the research has chosen the second view of the grammarians.